Carboxymethyl-lysine is a Prominent Target of Circulating IgA in IgA Nephropathy - Sara Alibrandi; Talita Aguiar; Mattea Ausmeier; Paolo Molinari; Enrico Fiaccadori; Umberto Maggiore; Nicholas Chun; Maria Lanau; Mario Perez-Arnedo; Joaquin Manrique; Paolo Cravedi; Emmanuel Zorn (Kidney International Reports)
Introduction: IgA nephropathy (IgAN), the most prevalent glomerular disease worldwide, carries a significant risk of kidney failure. Its pathogenesis involves the presence of elevated levels of IgA and galactose-deficient IgA (Gd-IgA), deposition of these antibodies in the kidney mesangium, and complement-mediated glomerular injury, leading to progressive renal function loss. The source and specificity of IgA in this disease remain unclear. We hypothesized that pathogenic IgA results from an immune response to abnormal protein modifications. Methods: We used an advanced enzyme-linked immunosorbent assay (ELISA) platform to assess serum IgA and Gd-IgA reactivity to 93 posttranslational modifications and other chemical adducts in 28 patients with biopsy-proven IgAN and 22 healthy controls. Results: Carboxymethyl-lysine (CML) was identified as the dominant target of IgA and Gd-IgA, but not IgG in patients with IgAN. This finding was validated in an independent cohort of 15 IgAN cases and 15 controls. In addition, a positive correlation was found between serum CML concentration and IgA reactivity in patients with IgAN, alongside albuminuria. Lastly, immunofluorescence staining observed elevated CML deposition in glomeruli of patients with IgAN than in controls. Conclusion: Our studies identify CML as a primary target of circulating IgA in IgAN, suggesting that aberrant responses to this modified self-antigen contribute to disease pathophysiology.